Development of Service Model for Uncontrolled Hypertension Clinic at Outpatient Department, Phu Ruea Hospital, Loei Province - Saenta, Buarisakorn (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
Hypertension is a major public health problem. Phu Ruea Hospital found that only 33.2% of patients could control blood pressure to target levels, lower than the Ministry of Public Health’s goal of 50%. Objectives: To study situation and factors affecting hypertension control, develop an effective service model, and evaluate effectiveness of the developed model. Methodology: This research and development study used a one-group pretest-posttest design. Samples were 72 uncontrolled hypertension patients at Phu Ruea Hospital outpatient department, selected by systematic random sampling from 819 eligible patients. Data were collected using questionnaires on knowledge (KR-20=0.91) and self-care behavior (Cronbach’s α=0.88), and standardized blood pressure measurements. Data were analyzed using descriptive statistics, paired t-test, McNemar’s test, and Cohen’s d effect size. Results: The developed model was “3-Phase Integrated Hypertension Care Model” consisting of: Phase 1-Screening, assessment and care planning; Phase 2-Intensive care and monitoring; Phase 3-Evaluation and plan adjustment. After 12-week implementation, knowledge scores increased from 10.8±3.6 to 17.2±2.1 (mean difference=6.4, 95%CI: 5.7-7.1, Cohen’s d=2.17, p<0.001), self-care behavior scores increased from 72.4±18.2 to 116.8±14.6 (mean difference=44.4, 95%CI: 39.2-49.6, Cohen’s d=2.69, p<0.001), systolic blood pressure decreased from 156.8±12.4 to 132.6±8.2 mmHg (mean difference=-24.2, 95%CI: -26.3 to -22.1, Cohen’s d=2.31, p<0.001), and diastolic blood pressure decreased from 96.2±8.6 to 82.4±6.4 mmHg (mean difference=-13.8, 95%CI: -15.3 to -12.3, Cohen’s d=1.82, p<0.001). Blood pressure control rate increased from 0% to 80.6% (p<0.001). All 72 participants completed the study with no dropout. Conclusion: The 3-Phase Integrated Hypertension Care Model demonstrated significant effectiveness in improving hypertension management outcomes. However, interpretation should consider the absence of a control group and potential regression to the mean effects. This model can be adapted for use in other community hospitals with similar contexts.